THE EXPANSION BECAUSE OF THE MEANING OF THE WORD IN AL KEFAYAH FI AL TAFSEER FOR ABI ABD AL-RAHMAN AL-HAIRY AL-NAYSABURI (D. 430 AH) - Alaa Abdulrazzaq Hardan; Assist. Prof. Dr. Haithem Taha Yassen (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
This research deals with the study of a great chapter that the Arabs followed in their speech, that inclusion of one word includes several meanings, all of which combine to serve the purpose of expression and to convey meanings in all their forms to the reader, This, in turn, adds to the touch of the Qur'anic miracles through the gorgeousness of his statement, which baffled the hearts and astonished the minds. I have taken from the books of interpretation and the books of the miracles of the Quran and the books of the vocabulary of the Holy Quran, a specific good for that. The research is divided into: First: The expansion in the verb. Second: The expansion in the name.